2017
DOI: 10.1021/acs.langmuir.6b04680
|View full text |Cite
|
Sign up to set email alerts
|

Janus Gold Nanoparticles from Nanodroplets of Alkyl Thiols: A Molecular Dynamics Study

Abstract: Janus particles provide an asymmetry in structure, which can impart diverse functionalities leading to immense importance in various applications, ranging from targeted delivery to interfacial phenomena, including catalysis, electronics, and optics. In this work, we present results of a molecular dynamics study of the growth mechanism of coating on gold nanoparticles (AuNPs) from droplets of n-alkyl thiols with different chain lengths (C5 and C11) and terminal groups (CH and COOH). The effect of chain lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Large, patchy, Janus-like domains can clearly be seen. This type of phase separation is consistent with previous simulation work that suggests that chemical mismatch induces patchy monolayer phase separation. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large, patchy, Janus-like domains can clearly be seen. This type of phase separation is consistent with previous simulation work that suggests that chemical mismatch induces patchy monolayer phase separation. , …”
Section: Resultsmentioning
confidence: 99%
“…Work by Glotzer et al and Stellacci et al used dissipative particle dynamics with a soft repulsive potential to model ligand monolayers. While these studies provide insight on the effects of physical and chemical mismatch on phase separation in the ligand monolayers, the simulations do not explicitly include attractive interactions between ligands or nanoparticle faceting, both of which have been shown to be important in subsequent work on NP , and flat monolayer phase separations. Other groups have modeled NP monolayers using molecular dynamics. , However, the equilibration of thiol monolayers in the laboratory can take up to 4 days, making it impossible for traditional molecular dynamics simulations to reach equilibrium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of the systems was controlled using Nosé–Hoover thermostat with a relaxation time of 0.1 ps. Previous works have also used successfully the same relaxation time for this thermostat . To investigate whether our systems have been achieved the equilibrium and stability, we have drawn the graphs of configurational energy, total energy, and temperature versus the simulation time for the different systems considered in this work and presented in Supporting Information Figures S5–S7.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…34,35 The chain length of the molecules is also a crucial factor in governing the structural behaviors of the adsorbed monolayers. 30,48 Longer chains promote enhanced molecular packing and ordering within the monolayers, leading to more well-defined and organized structures. 49 Previous studies demonstrated that alkanol molecules form a strongly adsorbed monolayer on a hydrophilic surface, such as mica.…”
Section: Introductionmentioning
confidence: 99%